2010
DOI: 10.3945/jn.109.112763
|View full text |Cite
|
Sign up to set email alerts
|

Snacking Increased among U.S. Adults between 1977 and 2006

Abstract: This study built on limited knowledge about patterns and trends of adult snacking in the US. We selected adults aged 19 y and older (n = 44,754) between 1977-1978 and 2003-2006 with results weighted and adjusted for sample design effects. Differences testing, by a Student's t test, used STATA 10 (P < or = 0.01). We defined a snacking event as intake of foods over a 15-min period and excluded food defined as snacks but eaten at a meal. Dietary data were obtained from the first 2 d for the 1977-1978 Nationwide F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
256
3
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(271 citation statements)
references
References 49 publications
9
256
3
3
Order By: Relevance
“…Admittedly, consumers' reliance on consumption norms may be particularly effective in conditions of diverted attention, such as when snacking while watching TV, because of decreased consumption monitoring (Higgs & Woodward, 2009;Wansink, 2004). A caloric increase caused by a CS variation may have important implications for body weight regulation, especially given that snacks have increased in energy density, frequency and contribution to daily caloric intake (Piernas & Popkin, 2010). In this view, researchers, health organizations and dieting programs have all recommended the use of smaller containers (Weight Watcher; National Institutes of Health, National Heart, Lung, and Blood Institute, 1999; U.S. Department of Agriculture, Center for Nutrition Policy and Promotion, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, consumers' reliance on consumption norms may be particularly effective in conditions of diverted attention, such as when snacking while watching TV, because of decreased consumption monitoring (Higgs & Woodward, 2009;Wansink, 2004). A caloric increase caused by a CS variation may have important implications for body weight regulation, especially given that snacks have increased in energy density, frequency and contribution to daily caloric intake (Piernas & Popkin, 2010). In this view, researchers, health organizations and dieting programs have all recommended the use of smaller containers (Weight Watcher; National Institutes of Health, National Heart, Lung, and Blood Institute, 1999; U.S. Department of Agriculture, Center for Nutrition Policy and Promotion, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings in our study, dinner was an important source of fish and vegetables, while snacks contributed substantially to fruit intake. Other studies have also found that fruits are a common component of snacks (18)(19)(20)(21) . However, the contribution of different meal types to intakes of different food items is likely to vary in different populations and population subgroups, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A representative survey in the US revealed that daily caloric intake from snacks increased from 357 kcal in the 1970s to 579 kcal in 2003-2006 (i.e. about 25% of the recommended daily intake; Piernas & Popkin, 2010). The situation is even worse in US children (2-19 years) for whom the percentage of kcal consumed from snacks per day increased from 24% in the 1970s to 36% in -2006(Piernas & Popkin, 2011.…”
Section: Adhering To Dietary Recommendationsmentioning
confidence: 96%